2014
DOI: 10.1080/13803395.2013.869309
|View full text |Cite
|
Sign up to set email alerts
|

To what extent does destination recall induce episodic reliving? Evidence from Alzheimer’s disease

Abstract: We compared destination memory to source memory in patients with Alzheimer's disease (AD), as the latter type of memory is believed to be severely deteriorated in AD. Control participants and AD patients were tested on two conditions, both of which had a study phase and a recognition phase. In the study phase of the first condition, participants had to tell a set of facts to the faces of a set of celebrities (destination memory). In the study phase of the second condition, they had to receive a different set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 32 publications
4
25
0
7
Order By: Relevance
“…In line with previous studies El Haj, Moroni, et al, 2014;El Haj, Postal, Le Gall, et al, 2013;Gopie et al, 2010), the older participants showed difficulties in destination recognition. They also showed decline in cognitive and affective theory of mind, a finding mirroring studies using the same tasks as the present work (Duval et al, 2011;Pardini & Nichelli, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous studies El Haj, Moroni, et al, 2014;El Haj, Postal, Le Gall, et al, 2013;Gopie et al, 2010), the older participants showed difficulties in destination recognition. They also showed decline in cognitive and affective theory of mind, a finding mirroring studies using the same tasks as the present work (Duval et al, 2011;Pardini & Nichelli, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…The celebrity faces and proverbs were taken from a large pool derived from previous studies assessing destination memory El Haj, Moroni, et al, 2014;El Haj, Postal, Le Gall, et al, 2013). As regards apparatus, DESTINATION MEMORY AND THEORY OF MIND 3 a laptop computer with a 15-inch LCD display was used for testing.…”
Section: Destination Memorymentioning
confidence: 99%
“…The study showed that patients with AD showed poor ability to retrieve specific autobiographical events, a distortion that was associated with a weakened ability to mentally relive those events (i.e., a decline in autonoetic consciousness). Disruption of autonoetic consciousness was also observed in subsequent replications that showed fewer “Remember” and more “Know” responses in AD participants than in healthy older adults (El Haj et al, 2014b; Hudon et al, 2009; Rauchs et al, 2007). With the passage of time, the repetition of similar events, and the advancement of the disease, a substantial loss of episodic autobiographical details is observed in AD.…”
Section: Autobiographical Memory Decline In Admentioning
confidence: 63%
“…AD-related autobiographical decline has been widely associated with a weakened ability to mentally reliving past events, and this decline has been demonstrated using the Remember/Know paradigm (El Haj et al, 2014b; Hudon et al, 2009; Rauchs et al, 2007). The study of autonoetic decline in AD requires specific rather than general assessment of subjective reliving.…”
Section: Summary and Suggestionsmentioning
confidence: 99%
“…The subjects had great difficulty in mentally reliving the events (i.e., they provided few “remember” responses), findings that were confirmed by subsequent studies. [31,3436] However, Madame F reported high visual imagery, auditory imagery, and mental time travel for flashbulb memories. To our knowledge, this is the first study to assess the subjective experience of flashbulb memories in AD.…”
Section: Discussionmentioning
confidence: 99%